SOCIAL MEDIA AND ADULT EDUCATION DELIVERY IN NIGERIA: A PARADIGM SHIFT - HUSSAIN, MUHAMMAD SHEHU (Sokoto Educational Review, 2022)
The paper examined social media and adult education delivery in Nigeria: a paradigm shift. Concepts of social media, adult education and blended learning were extensively discussed. Adult education as a flexible learning process accommodates innovations and creativity. Social media is seen as the most popular among younger and adult learners (females and males) and probably the most widely used in Nigeria. While blended learning is an introduction of online learning into a programme. Various forms of social media were highlighted which include amongst others Facebook, WhatsApp, Twitter, and Instagram, the characteristics of social media were extensively discussed; to demonstrate an e-presence, inform others about who you are, and what you do, and communicate and share ideas and experiences. The paper further explained how social media can be used in adult education and also discussed the positive effect of social media which include an increase in user familiarity with technology, learner support learning, and fun and easy creative ways to learn amongst others. The challenges of using social media in adult education were highlighted amongst others lack of stable infrastructure, cost and instability, and inadequately trained facilitators. The paper recommends the provision of alternative sources of power, reduction in the cost of internet services, and training and retraining of facilitators.